Using facebook as an alternative learning tool in Malaysian Higher Learning Institutions: a structural equation modeling approach - Haque, A. K. M. Ahasanul; Mohd. Israil, Khaliq Ahmad; Abdullah, Sarwar (World Academy of Science, Engineering and Technology, 2015)
Networking is important among students to achieve better understanding. Social networking plays an important role in the education. Realizing its huge potential, various organizations,including institutions of higher learning have moved to the area of social networks to interact with their students especially through Facebook. Therefore, measuring the effectiveness of Facebook as a learning tool has become an area of interest to academics and researchers. Therefore, this study tried to integrate and propose new theoretical and empirical evidences by linking the western idea of adopting Facebook as an alternative learning platform from a Malaysian perspective.